2020
DOI: 10.1051/0004-6361/201936821
|View full text |Cite
|
Sign up to set email alerts
|

Are ultra-diffuse galaxies Milky Way-sized?

Abstract: Now almost 70 years since its introduction, the effective or half-light radius has become a very popular choice for characterising galaxy size. However, the effective radius measures the concentration of light within galaxies and thus does not capture the intuitive definition of size which is related to the edge or boundary of objects. For this reason, we aim to demonstrate the undesirable consequence of using the effective radius to draw conclusions about the nature of faint 'ultra-diffuse galaxies' (UDGs) wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…In this regard, if anything, our measure for the size of galaxies could lead to slightly larger sizes where the efficiency of forming stars is higher than what we assume in this work (see Appendix A). On the contrary, if the star formation were very inefficient (as may well be the case for dwarf galaxies), our measure of size will be biased towards smaller sizes (see Chamba et al 2020). In Appendix B, we discuss the use of alternative proxies to locate the radial location of the gas density threshold for star formation.…”
Section: Towards a Physically Motivated Definition For The Size Of Gamentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, if anything, our measure for the size of galaxies could lead to slightly larger sizes where the efficiency of forming stars is higher than what we assume in this work (see Appendix A). On the contrary, if the star formation were very inefficient (as may well be the case for dwarf galaxies), our measure of size will be biased towards smaller sizes (see Chamba et al 2020). In Appendix B, we discuss the use of alternative proxies to locate the radial location of the gas density threshold for star formation.…”
Section: Towards a Physically Motivated Definition For The Size Of Gamentioning
confidence: 99%
“…For this reason, and as we will show in this work, galaxies with the same extension can have very different effective radii. This is not a minor issue and has serious consequences when one wants to address or infer the nature of galaxies (Chamba et al 2020). In addition, the R e of a galaxy can vary significantly with wavelength (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Using the publicly available catalog of 1 measurements from Trujillo et al ( 2020) and Chamba et al (2020) we find that 1 ≈ 7.8 , which implies that the normalization of the K13 relation in eq. E2,…”
Section: Appendix E: Using Other Size Estimatorsmentioning
confidence: 63%
“…Therefore, we expect ,80 ≈ 4.2 . Trujillo et al (2020) and Chamba et al (2020) used deep imaging of local galaxies to define 1 as the radius that encloses the region within a physically-motivated mass surface density of 1M pc −2 (see also SĂĄnchez Almeida 2020). Trujillo et al (2020) found that the scatter in the 1 − star relation is of the order of only ≈ 0.06 dex across five orders of magnitude, including the regime of MGs for which the relation, which is linear at lower masses, breaks.…”
Section: Appendix E: Using Other Size Estimatorsmentioning
confidence: 99%
See 1 more Smart Citation